Students' Social Attitudes Towards German and The German Language in Traditional and Innovative Teaching of German as a Foreign Language at The Faculty of Philosophy in Novi Sad - Ana Stipančević (University of Belgrade, 2020)
The study of attitudes plays an important role in the field of social psychology, but also in the field of language teaching theory, since attitudes towards the nation, language, and teaching itself affect the motivation for language learning, and thus academic achievement. The goal of modern foreign language teaching is not only to develop students' communicative, but also their intercultural competence, which includes the ability to make contact with members of other cultures, the ability to compare their own and foreign cultures, as well as overcoming cultural conflicts and misunderstandings. Teaching a foreign language has, therefore, a task to connect people and build bridges between cultures.